Development of the Adapted Pivot Test method for descriptive sensory analyses with young untrained students. Issue 5 (3rd August 2022) - Beaulieu, Aleksandr; Giraud, Valentin; Magro, Pierre; Nougarede, Sylvain; Maza, Elie; Samson, Alain; Geffroy, Olivier; Chervin, Christian
Abstract: A recent method using paired comparison between coded wines and a pivot wine, first developed with wine experts, was adapted to be performed by students, as potential young consumers. The untrained students generated the list of words in a preliminary session, and then a paired comparison with a pivot wine was performed, using the words representing 75% of total occurrences. Correspondence analyses enabled the categorization of either white or red wines, using the respective words chosen by students. These correspondence analyses (CA) enable to associate wines and words as expected, but also grouped similar wines that were presented under different codes, as a test. And CA also logically discriminated words, such as "intense, " "lingering, " and "burning, " from "light" and "fresh, " which are indeed opposed in food sensory perception. A statistical approach, using the chi‐squared test of independence, is also proposed to determine the optimal panelist number. Practical applications: Our results suggest that this method, called Adapted Pivot Test (APT), could be useful for descriptive analyses by untrained students. The method could provide simple means for categorizing products, without using semantic analyses, which often create biases when performed by nonspecialists. The robustness of this method could be further tested using various products and consumer panels. In addition, we provide a full set of data that can be used in sensory analysis or statistical teaching courses.